PERFORMANCE EVALUATION OF LQ45 STOCKS IN THE INDONESIA STOCK EXCHANGE DURING PERIOD OF 2016-2018 - Happy Catherine; Robiyanto Robiyanto (Journal of Management and Entrepreneurship Research, 2020)
Objective: This study investigates the performance evaluation of each LQ45 stock in the Indonesia Stock Exchange conducted by using the Sharpe Index, Treynor Ratio, Jensen Alpha, Sortino Ratio, and Information Ratio. Stocks evaluated are those that consistently listed in the LQ45 index during 2016-2018. Research Design & Methods: The number of samples used in this study was 32 stocks taken using a purposive sampling technique. The data used in this study are the monthly closing price of stocks, the composite stock price index, and the BI 7-day Repo Rate interest rate data. Findings: The results of this study show that not all stocks included in the LQ45 index have good performances. The results of this study show that BBCA stock is the best stocks based on Sharpe Index and Information Ratio. Based on the Jensen Alpha method and the Sortino Ratio, PTBA stock is the best stocks. As for the Treynor Ratio method, the best stock is INCO. Recommendations: There is a blemish in research for further research that is expanding the scope of research, not only companies included in LQ45. Future studies can analyze portfolios consisting of LQ45 stocks and updating periods because stock performance is cyclical. Contribution & Value Added: This research contributes to the analysis of LQ45 stock performance based on five methods including Sortino and Information Ratio that are rarely used and show differences in the results of the five stock performance indices.